Quality of Sleep and Psychological Distress in Glaucoma - Ogunsemi OO; Bodunde OT; Afe TO; Oyelekan AA; Shorunmu TO; Onabolu OO; Abasiubong F (Annals of Health Research, 2016)
Background: People living with glaucoma are psychologically burdened because of the threat of visual loss. Therefore, understanding the psychosocial issues and quality of sleep holds important implications for the recognition, prevention, and treatment of emotional problems among people with glaucoma. This study investigated the quality of sleep and psychological distress among people with glaucoma.